2004
DOI: 10.3766/jaaa.15.6.5
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Directional Microphones for Hearing Aids: Real-World versus Simulation

Abstract: The purpose of this study was to assess the accuracy of clinical and laboratory measures of directional microphone benefit. Three methods of simulating a noisy restaurant listening situation ([1] a multimicrophone/multiloudspeaker simulation, the R-SPACE, [2] a single noise source behind the listener, and [3] a single noise source above the listener) were evaluated and compared to the "live" condition. Performance with three directional microphone systems differing in polar pattern (omnidirectional, supercardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 14 publications
1
80
0
Order By: Relevance
“…R-Space TM ) has been introduced that accurately recorded and then reproduced/simulated a real-world restaurant for hearing-aid evaluations (Revit et al, 2002). A recent study by Compton-Conley et al (2004) reported that the performance of omnidirectional and directional microphones were similar when measured 'live' and in the 'laboratory' with this system. Thus, this new system may provide the researcher and clinician with a tool that provides greater external validity of hearing-aid performance when measured in the laboratory or clinic.…”
Section: Sumariomentioning
confidence: 79%
See 1 more Smart Citation
“…R-Space TM ) has been introduced that accurately recorded and then reproduced/simulated a real-world restaurant for hearing-aid evaluations (Revit et al, 2002). A recent study by Compton-Conley et al (2004) reported that the performance of omnidirectional and directional microphones were similar when measured 'live' and in the 'laboratory' with this system. Thus, this new system may provide the researcher and clinician with a tool that provides greater external validity of hearing-aid performance when measured in the laboratory or clinic.…”
Section: Sumariomentioning
confidence: 79%
“…In this study, Compton-Conley et al (2004) reported (Figure 4, page 447) that the long-term speech spectra of the HINT sentences, HINT noise, and R-Space TM noise was very similar between approximately 500 to 8000 Hz. It is important to note that the Compton-Conley et al (2004) study was based on a smaller subject sample (N 012), normal-hearing listeners, and hearing aids that differed significantly from the hearing aids used in the current study.…”
Section: R-space Tm Restaurant Noisementioning
confidence: 82%
“…The poorest SNR possible was 23.5 dB. The Hearing In Noise Test (Nilsson, Soli, & Sullivan, 1994) was presented in restaurant noise (Compton-Conley, Neuman, Killion, & Levitt, 2004) at 60 dB SPL using the R-Space (Revit, Schulein, & Julstrom, 2002). The R-Space is a system with eight loudspeakers positioned 360°around the participant, each 24 in.…”
Section: Sound-field Detection Threshold and Speech Recognition Measuresmentioning
confidence: 99%
“…Signal delivery was accomplished with the R-SPACE (Revitronix, Braintree, VT) sound-simulation system (for greater detail, see Compton-Conley, Neuman, Killion, & Levitt, 2004). This system consists of an eight-loudspeaker array, which is placed in a circular pattern around the subject.…”
Section: Test Environmentmentioning
confidence: 99%